2003
DOI: 10.1111/1467-8306.9303004
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Spatial Analysis in Geographic Information Systems

Abstract: A common-perhaps modal-representation of geography in spatial analysis and geographic information systems is native (unexamined) objects interacting based on simple distance and connectivity relationships within an empty Euclidean space. This is only one possibility among a large set of geographic representations that can support quantitative analysis. Through the vehicle of GIS, many researchers are adopting this representation without realizing its assumptions or its alternatives. Rather than locking researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 151 publications
(115 reference statements)
0
64
0
2
Order By: Relevance
“…Here, p can be chosen to approximate known distance types. For example, Miller and Wentz (2003) show that TT in an urban setting could be represented by p values ranging from 1 to 2. Furthermore, as each individual GWR calibration is independent from each other, it would be straightforward to apply parallel computing techniques (e.g.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, p can be chosen to approximate known distance types. For example, Miller and Wentz (2003) show that TT in an urban setting could be represented by p values ranging from 1 to 2. Furthermore, as each individual GWR calibration is independent from each other, it would be straightforward to apply parallel computing techniques (e.g.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…For example, Shahabi et al (2002) and Shahid et al (2009) use Minkowski distance to approximate road distances and TTs. Love et al (1988), cited by Miller and Wentz (2003), indicate that the value of p typically ranges from 1 to 2 for representing the true travel distance at urban and regional scales. For a spatial model that is adapted to use Minkowski distances, optimal values of p and θ are commonly found that minimize some goodness-of-fit (GoF) criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The most common perspective is to replace the Euclidean distance measures with network distances (Miller and Wentz 2003). Spatial optimization models often treat network distances between locations either as a quantitative measure such as in a point location model (Church and Murray 2008b) or as a virtual link network that is transformed from relationships between neighboring objects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is little here to suggest a sustained research theme of alternative models of space. As Mark and Frank note, "except for geodesics on cost surfaces, nonEuclidean geometries have not made significant inroads into mainstream geographic models" (1996,17), a claim substantially true today, which also hints at the crux of the problem: the lockin effects of existing GIS, regardless of the efforts of GIScientists (Miller and Wentz 2003). Of course, computation does require reduction and abstraction of events to textual, numeric, or otherwise programmatically understood representations (Ullman 1997, Drucker 2009).…”
Section: Points To Graphsmentioning
confidence: 99%